2015
DOI: 10.1039/c5cc02594j
|View full text |Cite
|
Sign up to set email alerts
|

Ebselen as a potent covalent inhibitor of New Delhi metallo-β-lactamase (NDM-1)

Abstract: We report the discovery of a promising NDM-1 inhibitor, ebselen, through a cell-based screening approach. Enzymatic kinetic study and ESI-MS analysis suggested that ebselen could bind to NDM-1 by forming a S-Se bond with the Cys(221) residue at the active site, thereby exhibiting a new inhibition mechanism with broad spectrum inhibitory potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 38 publications
3
75
0
1
Order By: Relevance
“…Representative inhibitors of NDM-1 [28][29][30][31][32][33][34][35][36]. ChemMedChem 2019, 14,1271 -1282 www.chemmedchem.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim 3, 5, 6,a nd 8 are summarized in Scheme 2.…”
mentioning
confidence: 99%
“…Representative inhibitors of NDM-1 [28][29][30][31][32][33][34][35][36]. ChemMedChem 2019, 14,1271 -1282 www.chemmedchem.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim 3, 5, 6,a nd 8 are summarized in Scheme 2.…”
mentioning
confidence: 99%
“…The notion of the involvement of interactions other than electrostatic derives further support from the observation that the replacement of arginine by lysine residues resulted in the abolishment of the peptides' inhibitory potency. which has been shown to not only inactivate NDM-1 and VIM-2, but also reverse carbapenem resistance in vivo [81]; (iv) ebselen, a seleno compound which targets Cys221 in NDM-1 resulting in the loss of one of its zinc ions [82]; and (v) clinically already approved thiolcontaining drugs which have been found to inhibit NDM-1, VIM-1 and IMP-7 in the low micromolar range [83]. The arginine-containing peptides described in the current report add to this list because they not only serve as very potent (nanomolar) inhibitors of VIM-2 (and potentially other MBLs), but also appear to be unique in that they trigger aggregation of the enzyme (at least at the concentrations employed for the spectroscopic investigations).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is worth mentioning that Chiou proposed a selenium‐containing inhibition called ebselen (Figure .20), which has been shown to effectively inactivate NDM‐1 and restore meropenem activity on NDM‐1. Electrospray ionization mass spectrometry (ESI‐MS) analysis indicated that it can bind to NDM‐1 by forming an S‐Se bond at the active site with the Cys221 residue (Chiou et al., ).…”
Section: Progress In Designing Metallo‐β‐lactamase Inhibitorsmentioning
confidence: 99%